''Near Miss'' Obstetric Cases: 4 Years Experience of a Tertiary Center - Hüseyin Cengiz; Cihan Kaya; Ramazan Ateş; Yusuf Ziya Yener; Murat Ekin; Levent Yaşar (Medical Network, 2016)
OBJECTIVE: To evaluate the frequency of near miss and the nature of near miss events, and comparatively analyze near miss morbidities among pregnant women managed in our institution over a 4-year period. STUDY DESIGN: The study was conducted in Bakırköy Dr. Sadi Konuk Education and Research Hospital. Cases were identified through a retrospective analysis of hospital records of pregnancy-related complications reported between January 1, 2008 and December 31, 2011. For each case of near miss morbidity and maternal death, data on demographic characteristics were collected, including the patient's age, parity, previous deliveries, and gestational age at delivery. Data on the nature of obstetric complications, the location where they developed (home, private doctor's office, maternity center, or hospital), type of delivery, fetal outcomes, and length of stay in the intensive care unit (ICU) were collected. RESULTS: During the study period, 6833 adults required ICU admission; 41 (0.60%) of them were obstetric patients. The total number of births reported during the study period was 9841. The mean age of the patients was 28.5 years (range, 17-52). Six women (14.6%) were admitted before and 35 (85.4%) after childbirth. The most common diagnosis was preeclampsia (41.5%), followed by obstetric hemorrhage (29.2%). CONCLUSION: Maternal health care policies need to be concerned with preventing near miss cases.